PERANCANGAN PERANGKAT LUNAK PENDAFTARAN DAN PENJADWALAN UJIAN SKRIPSI PADA FAKULTAS KEDOKTERAN UNIVERSITAS PALANGKA RAYA BERBASIS WEBSITE (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Thesis is a scientific essay that is required as part of academic education requirements. Thesis is arranged and maintained to achieve a bachelor's degree at a tertiary institution, done according to certain rules and procedures. Thesis registration at the Faculty of Medicine, University of Palangka Raya still uses a manual system, where the submission of titles is still using paper forms and students are asked to fill out a research registration form. Students must meet the P2M Section to submit a research title. Information about the seminar schedule is still posted on the bulletin board so students must come to campus to view seminar schedule information. To overcome these problems, a study was made, namely Analysis and Design of Software Registration and Scheduling of Thesis Examinations at the Faculty of Medicine, University of Palangka Raya Website Based with the stages of research divided into two stages, namely: (1) literature study and (2) software development by applying modified waterfall method which includes four steps namely system analysis, design, implementation and testing. For implementation using PHP in making program code and Mysql as a database to store data. Furthermore, software testing uses Blackbox testing. This software has facilities to support the progress of the thesis process at the Faculty of Medicine, Palangka Raya University, namely: (1) Submission of Research Proposals, (2) Registration of Research Proposal Seminars and Registration of Thesis Exams, (3) Scheduling of Research Proposal Seminars and Scheduling Exams Thesis. Users of this software are twofold, namely the P2M and Student Sections. Based on the results of tests conducted on users, it can be seen that this software can run well.